Clinico-Pathological Study of Abdominal Hysterectomies - Naher, Lutfun; Parvin, Zebunnessa; Khanam, Shafeya; Rosy, Nasrin (Faridpur Medical College Journal, 2018)
Hysterectomy is the commonest gynaecological operation. It is still considered as the treatment of choice for benign lesion such as leiomyoma, adenomyosis, extensive pelvic infection or adhesions, dysfunctional uterine bleeding and obstetric complications. A Cross-sectional observational study was done in the Department of Obstetrics and Gynecology during the period from 1st January to 31st December 2015 at Faridpur medical college and hospital, Faridpur. This study was done to correlate the indications of abdominal hysterectomy to histopathological findings thus, determining histologically confirmed preoperative clinical diagnosis. One hundred patients undergoing abdominal hysterectomy were studied. Data were recorded on structured proforma, including demographic characteristics, clinical features and indications of the procedure. In this study, leiomyoma of the uterus was found to be the major indication of hysterectomy in 35% of total cases, followed by dysfunctional uterine bleeding (DUB) in 26%, and pelvic inflammatory disease (PID) in 6%. Histopathological confirmation of pre-operative diagnosis was 100% for malignancy, 85.71% for fibroid and 65.38% for DUB. Hysterectomy is currently the most widely performed major operation in gynecology and histopathology is mandatory for ensuring diagnosis and management of malignant diseases. Faridpur Med. Coll. J. Jan 2018;13(1): 28-30